The Influence of Service Quality on Purchase Decision with Brand Image as an Intervening Variable at Pop Hotel Diponegoro Surabaya - Sudirman, Maya Paramitha Dewanty; Herdinata, Christian (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to determine the effect of service quality on consumer purchase decisions through brand image as an intervening variable at POP Hotel Diponegoro Surabaya. The variables studied were service quality (X), brand image (M), and purchase decision (Y). Service quality has five indicators, namely reliability, responsiveness, assurance, empathy, and tangibles. Brand image has three indicators, namely the superiority of brand associations, the uniqueness of brand associations, and the strength of brand associations. Purchase decisions have four indicators, namely the stability of buying after nowing product information, deciding to buy because the brand is the most preferred, buying because it suits their wants and needs, and buying because they get recommendations from others. The population in this study were all consumers at POP Hotel Diponegoro Surabaya. The number of respondents in this study was 120 people with the criteria of respondents who decided to stay at POP Hotel Diponegoro Surabaya at least once and aged 17-65 years. This study uses a quantitative approach with data processing techniques using SEM-PLS. The results of the study show that service quality has a significant effecton purchase decision; brand image has a significant effect on purchase decision; service quality has a significant effect on brand image; and service quality has a significant effect on purchase decision through brand image as an intervening variable.